A privacy-friendly architecture for future cloud computing. (1st January 2013) - Petrlic, Ronald; Sekula, Stephan; Sorge, Christoph
We present a privacy-friendly architecture for a future cloud computing scenario where software licensing and software payment plays a major role. We show how digital rights management as a technical solution for software licensing can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers and execute it at computing centres stay anonymous. At the same time, our approach guarantees that software licences are bound to users and that their validity is checked before execution. Thus, digital rights management constitutes an incentive for software providers to take part in such a future cloud computing scenario. We employ a software re-encryption scheme so that computing centres are not able to build profiles of their users – not even under a pseudonym. We make sure that malicious users are unable to relay software to others.